Underwater Seascapes From geographical to ecological perspectives - Musard, Olivier; Le Dû-Blayo, Laurence; Francour, Patrice; Beurier, Jean-Pierre.; Feunteun, Eric.; Talassinos, Luc.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
While the European Landscape Convention adopted in Florence in 2000 by the European Council offers a public-action framework through a normative definition, the marine and submarine dimensions of landscapes are attracting growing interest from researchers worldwide. At a time when marine-conservation objectives are strongly endorsed by the Convention on Biological Diversity, the French Marine Protected Areas Agency, a public institution under the governance of the French Ministry of the Environment, has gathered prominent experts to draft the very first interdisciplinary overview of underwater seascapes, so as to initiate and lend direction to a wider reflection on this emerging research topic.
PART I: Exploring the diversity of underwater seascape representations and frameworks -- Part II: Towards landscape ecology applied to the marine area -- Part III: Tools, methods and instruments for monitoring and modelling underwater seascapes.
Keywords: Marine sciences; Freshwater; Marine & Freshwater Sciences